Membangkitkan Energi Spiritual dalam Pengajaran - Siti Asdiqoh (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2009)
Raising spiritual energy in teaching is actually the output of voluntarily process to perceive teacher professionalism as the best profession given by the Almighty God, Allah SWT. The process can be achieved through spiritual accomplishments originating from opening, managing, and functioning heart. The heart voice is the center of true intuition. Heart tends to good deed that does not contradict with true principles and values. The totality teaching accomplishment is the teacher efforts to teach in accordance with the common student potential. In fact, teaching professionally may interest students. Personalities framed by the goodness may bring about teacher affection to students and make them treating their students as their children.